Environmental history in the school textbooks of technical institutes - Elia, Domenico Francesco Antonio (Rivista di Storia dell’Educazione, 2023)
The author analyses the adoption of history textbooks in grades 11-13 of Italian Technical Institutes during the school year 2022/2023, considering national and international secondary literature. The paper aims to evaluate the extent to which history textbooks cover topics of environmental history by investigating a sample of textbooks widely adopted in these schools. On the basis of the results, the author highlights issues regarding updating textbooks to current academic research. In addition, he formulates proposals to increase the presence of environmental history and enhance the connections between individuals, societies and the Earth following a planetary education (Morin 2016).